Design and Implementation of Image Fusion System - Mishra, Vikas Kumar; Kumar, Shobhit; Gupta, Ram Kailash (International Journal of Computer Sciences and Engineering, 2014)
Image fusion can be broadly defined as the process of combining multiple input images or some of their features into a single image without the introduction of distortion or loss of information. The aim of image fusion is to integrate complementary as well as redundant information from multiple images to create a fused image output. We introduce the basic principles of image fusion at pixel level, feature, and decision. Design rules and steps of graphical user interface (GUI) are described. Image fusion system based on graphical user interface has been designed and implemented below. We give you part of the overall design of the system and explain their method of use. The system has many functions: image denoising, image enhancement, image registration, image segmentation, image fusion, and evaluation of the merger.